2003
DOI: 10.1111/j.1748-720x.2003.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain Relief, Prescription Drugs, and Prosecution: A Four-State Survey of Chief Prosecutors

Abstract: The experience of having to suffer debilitating pain is far too common in the United States, and many patients continue to be inadequately treated by their doctors. Although many physicians freely admit that their pain management practices may have been somewhat lacking, many more express concern that the prescribing of heightened levels of opioid analgesics may result in closer regulatory scrutiny, criminal investigation, or even criminal prosecution.Although several researchers have examined the regulatory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…A limitation of our work is that in addition to state medical boards and the DEA, state and county authorities [19,20] can initiate legal actions against physicians who prescribe opioids. A survey of chief prosecutors from Connecticut, Maryland, Oregon, and Washington found that given a scenario of opioid treatment of a patient with chronic nonmalignant pain, some of the prosecutors would recommend a police investigation to determine whether diversion were occurring while most said they probably would not [21]. Additional reviews of state and county officials activities are needed for a more thorough assessment of the physician’s risk of a punitive action by government for prescribing opioids for patients in pain.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of our work is that in addition to state medical boards and the DEA, state and county authorities [19,20] can initiate legal actions against physicians who prescribe opioids. A survey of chief prosecutors from Connecticut, Maryland, Oregon, and Washington found that given a scenario of opioid treatment of a patient with chronic nonmalignant pain, some of the prosecutors would recommend a police investigation to determine whether diversion were occurring while most said they probably would not [21]. Additional reviews of state and county officials activities are needed for a more thorough assessment of the physician’s risk of a punitive action by government for prescribing opioids for patients in pain.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, it is the perceived, not the actual, risk that is likely to drive behavior. In the area of pain management, for example, physicians commonly cite fear of criminal liability as a barrier to aggressively prescribing narcotics (Ziegler and Lorich 2003), despite the fact that criminal actions against physicians who prescribe narcotics appropriately are fairly rare events (Meier 2008).…”
Section: Changing the Incentives: Legal Measures To Promote Conservatmentioning
confidence: 99%
“…241 The agency has stated that the “types of cases in which physicians have been found to have dispensed controlled substances improperly under federal law generally involve facts where the physician’s conduct is not merely of questionable legality, but instead is a glaring example of illegal activity.” 242 While isolated examples of overreaching prosecutors exist, 243 there are no recent data regarding prosecutors’ decisions to charge physicians. A 2003 study revealed a number of prosecutors surveyed understood the complexity of misprescriber situations; 244 however, the majority of prosecutors did not regard physicians as effective self-regulators. 245 The prosecutors ranked deceptive patients as the largest source of diversion, followed by impaired, dated, and dishonest doctors, respectively.…”
Section: Regulation Of Medical Practice and Prescribingmentioning
confidence: 99%